The Importance of Job Satisfaction in Mediating Employee Retention at Dewi Sri Hospital - Fahad Fahad; MF Arrozi Adhikara; WD Purwati (Alta Dharma Publisher, 2021)
Introduction: Employee retention is an effort to maintain to stay in the organization to achieve the goals of the organization. Employee retention is said to be good if a company can retain its potential employees to remain loyal to the company for a longer period. Several factors affect employee retention, including workload, job satisfaction, and burnout. Objective: The study aimed to analyze the effect of workload on employee retention with burnout and job satisfaction as intervening factors at Dewi Sri Hospital. Method: A quantitative analytic with a cross-sectional design approach was applied in this study. approach was applied in this study. A total A total of 224 samples were selected based on the inclusion criteria. were selected based on the inclusion criteria. Results: The results found that Workload, Burnout, and Job Satisfaction were significantly effect on staff performance. Conclusion: The employee retention among staff by managing the workloads to prevent fatigue and burnout and increase job satisfaction. Recommendation: Further study need to conduct the similar study with expand the method and different setting to ensure the feasibility of the study